2021
DOI: 10.3174/ajnr.a7216
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor versus Clopidogrel in the Dual Antiplatelet Regimen for Intracranial Stenting or Flow-Diverter Treatment for Unruptured Cerebral Aneurysms: A Single-Center Cohort Study

Abstract: BACKGROUND AND PURPOSE: Ticagrelor is a novel P2Y12 antagonist, and little is known about its efficacy and safety in the endovascular treatment of aneurysms. This study evaluated the efficacy and safety of ticagrelor versus clopidogrel for stent-assisted coiling or flow-diversion treatment in patients with unruptured cerebral aneurysms. MATERIALS AND METHODS:From November 2003 to February 2019, two hundred one patients (mean age, 57.5 years; 156 women) with 233 unruptured aneurysms underwent stent-assisted coi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…All studies were published between 2017 and 2021. Of the 10 studies, 2 [ 21 , 22 ] were multicenter and 8 [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] were single-center, involving a total of 1377 patients receiving endovascular therapies for aneurysms from six countries with sample sizes ranging from 78 to 321, including 1 [ 24 ] RCT study, 1 [ 23 ] prospective cohort study and 8 [ 21 , 22 , 25 , 26 , 27 , 28 , 29 , 30 ] retrospective cohort studies. Endovascular therapies contain spring coil embolization, stent assisted coil embolization and flow diverter procedures, perioperative and postoperative with clopidogrel or ticagrelor antiplatelet therapy; 4 [ 22 , 23 , 28 , 29 ] of the studies tested for platelet function and changed the antiplatelet regimen to ticagrelor in patients with clopidogrel resistance.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All studies were published between 2017 and 2021. Of the 10 studies, 2 [ 21 , 22 ] were multicenter and 8 [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] were single-center, involving a total of 1377 patients receiving endovascular therapies for aneurysms from six countries with sample sizes ranging from 78 to 321, including 1 [ 24 ] RCT study, 1 [ 23 ] prospective cohort study and 8 [ 21 , 22 , 25 , 26 , 27 , 28 , 29 , 30 ] retrospective cohort studies. Endovascular therapies contain spring coil embolization, stent assisted coil embolization and flow diverter procedures, perioperative and postoperative with clopidogrel or ticagrelor antiplatelet therapy; 4 [ 22 , 23 , 28 , 29 ] of the studies tested for platelet function and changed the antiplatelet regimen to ticagrelor in patients with clopidogrel resistance.…”
Section: Resultsmentioning
confidence: 99%
“…In the meta-analysis of perioperative and postoperative application of clopidogrel or ticagrelor in patients with aneurysms after endovascular interventional surgery, 10 studies were included in the thromboembolic complications analysis; 5 [ 21 , 22 , 24 , 26 , 30 ] studies showed a decreased trend toward thromboembolic complications compared with the clopidogrel group, and 5 [ 23 , 25 , 27 , 28 , 29 ] studies showed a poorer trend. The results of the pooled 10 studies showed that, like clopidogrel, ticagrelor had a good prevention efficacy in the analysis of the efficacy of thromboembolic events; there was no significant difference (RR = 1.14, 95% CI: 0.76–1.72, p = 0.52).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three to 5 days before the endovascular procedure, dual antiplatelet therapy was administered for all patients with clopidogrel (75 mg/d) and aspirin (100 mg/d) ( 24 ). The endovascular procedure was conducted under general anesthesia and heparinization.…”
Section: Methodsmentioning
confidence: 99%